Etnopedagogi Sebagai Media Pelestarian Kearifan Lokal Dalam Pembelajaran Biologi - I Wayan Suanda; I Made Subrata; Kadek Intan Rusmayanthi (Emasains : Jurnal Edukasi Matematika dan Sains, 2024)
The culture of a nation goes hand in hand with civilization in people's lives. Culture, customs and natural resources of a nation as local wisdom have the potential to be developed and preserved through ethnopedagogy. Ethnopedagogy is the inculcation of the local wisdom’s value of a nation or region that needs to be introduced by revitalizing it for the advancement of civilization. Ethnopedogogy research, as a medium for preserving local wisdom in biology learning, aimed to re-introducing the culture of the region where the learners come from as local wisdom to foster a sense of love and foster self-confidence in existing cultures. The implementation of local wisdom in biology learning is expected to be able to instil character education in order to create Pancasila students. Budaya suatu bangsa berjalan seiring dengan peradaban dalam kehidupam masyarakat. Budaya, adat istiadat dan kekayaan alam suatu bangsa sebagai kearifan lokal yang berpotensi dikembangkan dan dijaga kelestariannya melalui etnopedagogi. Etnopedagogi merupakan penanaman nilai kearifan lokal suatu bangsa atau daerah perlu diperkenalkan dengan melakukan revitalisasi untuk kemajuan peradaban. Penelitian etnopedogogi sebagai media pelestarian kearifan lokal dalam pembelajaran biologi, memiliki tujuan mengenalkan kembali budaya daerah tempat peserta didik itu sebagai kearifan lokal untuk menumbuhkan rasa cinta dan menumbuhkan rasa percaya diri pada budaya yang telah ada. Implementasi kearifan lokal dalam pembelajaran biologi diharapkan mampu menanamkan pendidikan karakter agar tercipta pelajar Pancasila.